Some lessons for the CSME from the retail banking sector in the European Single Market - Campbell Gill, Michelle ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 2007)
Examines trade in retail banking services in the European Union and seeks to derive lessons for the Caribbean in this regard.